The changing role of the international community in the achievement of the MDG goals in Bolivia - Massimiliano Calì; Luis Carlos Jemio M. (Institute for Advanced Development Studies (INESAD), 2010)
Millennium Development Goal number 8 (MDG8) concerns those external flows (Official Development Assistance, trade and debt relief) that ought to help developing countries achieve the MDGs by 2015. This paper reviews the role of these MDG8-related external flows in the case of Bolivia. Riding on high international prices for its major exports, and on fiscal expansion, remittances and debt forgiveness, Bolivia has experienced solid economic performance in the past few years. This economic performance coupled with the recent increase in social public expenditures by the government has increased the likelihood that the country will achieve all of the MDGs by 2015, except probably for MDG 2. These advances have been achieved in a period of radical change in Bolivia's dependence on MDG8-related external flows. The composition of external finance in public expenditure has shifted from domination by ODA and debt forgiveness in the first half of the decade to domination by trade, mainly through revenues from hydrocarbon exports. Our findings support the idea that the provision of additional financial resources may not be the priority with regard to organising support to MDG achievements. Spending efficiently and effectively seems to be a more important area for support in Bolivia. As far as trade is concerned, Bolivia already enjoys good market access in its main markets, thus better access through lower non-tariff barriers may be more relevant than improving access in terms of tariffs. Moreover access to markets would be easier if Bolivia were better integrated with world markets, with its regional neighbours in particular. This calls for the support of the international community through aid for trade (AfT), which has instead been worryingly dwindling in recent years. Finally, we argue that MDG8 could be pursued in Bolivia through support for improving access to technology and access to affordable drugs.
Keywords: F35; O11; O54; P45; 330; Bolivia; MDGs; aid; trade; debt; Entwicklungshilfe; Millennium Development Goals; Bolivien